Public Administration’s Regulatory Acts: Classification Issues - V. R. Bila (Bulletin of Kharkiv National University of Internal Affairs)
The author has attempted to group public administration’s normative acts. The advantages of classification as the method of cognition of state and legal phenomena and rules of its conduction have been outlined. The criteria for classification of public administration’s regulatory acts have been clarified. That made it possible to specify the content of the components identified as a result of the classification. The author has emphasized the necessity of forming theoretical system of regulatory acts as forms of public administration, establishing their clear hierarchy and competent independence.